Infodemia y desinformación en la pandemia por la COVID-19: percepciones e impacto de las fake news en adultos jóvenes de Lima Metropolitana - Martínez Palomino, Jessica (2023)
This study analyzes the perceptions of the credibility of fake news regarding COVID-19 and disseminated through social networks in young adults aged 20 to 35 who belong to the socioeconomic group B of Metropolitan Lima, Peru. A significant fraction of this population represents half of the country’s workforce and are household decision-makers. The goal is to determine the elements that contribute credibility to fake news, the factors that enable them to be recognized, and their influence in decision-making on health, vaccination, and prevention practices. The methodological proposal is based on the analysis of fake news verified by the local fact-checker Ojo Biónico and survey technique. I consider the type of fake news that Wardle and Derakhshan (2017) elaborated on in the analysis. The survey includes two exercises to describe the ability to recognize fake news and one exercise for assessing the graphic, text and communication elements that allow Fake News to be detected. Based on survey responses collected for this study, I conclude that the confidence level in mass media and social network platforms is intermediate. Similarly, the influence of fake news regarding vaccination on the participant's opinions and perceptions is moderate. As indicated by survey participants, social media platforms are the most used media outlet and the primary transmitter of unreliable content. Less than half of the participants correctly identified information and disinformation content. This indicates that the participants have digital citizenship skills, but is necessary to work on them through a carefully designed training.